Python Web Scraping Cookbook : Over 90 proven recipes to get you scraping with Python, micro services, Docker and AWS. - Heydt, Michael (Packt Publishing, 2018)
Python Web Scraping Cookbook is a solution-focused book that will teach you techniques to develop high-performance Scrapers, and deal with cookies, hidden form fields, Ajax-based sites, proxies, and more. By the end of this book, you will be able to scrape websites more efficiently with more accurate data, and how to package, deploy and ...